Consumer perspectives on the use of ai in the fashion industry in Malaysia - Nadeem, Soha (2023)
Adoption of technology and use of AI has increased significantly in the retail world post-COVID-19, and hence global retailers are aiming for greater AI integration in order to align their products and services with customer expectations and preferences. In the fashion industry, AI is serving as an excellent tool to meet the rapidly changing customer demands, as well as to increase sales efficiency. Therefore, understanding consumer responses to AI has become critical for retailers to effectively maintain a significant competitive advantage and overall improve their marketing practices.